Craving and opioid use disorder: A scoping review. (1st December 2019) - Kleykamp, Bethea A.; De Santis, Marta; Dworkin, Robert H.; Huhn, Andrew S.; Kampman, Kyle M.; Montoya, Ivan D.; Preston, Kenzie L.; Ramey, Tanya; Smith, Shannon M.; Turk, Dennis C.; Walsh, Robert; Weiss, Roger D.; et al.
Highlights: Craving for opioids is a common patient-reported experience. Fifteen opioid craving assessment instruments were identified in the published literature. Few of the available opioid craving assessments have been evaluated for reliability and validity. Validated opioid craving assessments could help guide the development of new OUD treatments. Abstract: Introduction: The subjective experience of drug craving is a prominent and common clinical phenomenon for many individuals diagnosed with opioid use disorder (OUD), and could be a valuable clinical endpoint in medication development studies. The purpose of this scoping review is to provide an overview and critical analysis of opioid craving assessments located in the published literature examining OUD. Method: Studies were identified through a search of PubMed, Embase, and PsychInfo databases and included for review if opioid craving was the focus and participants were diagnosed with or in treatment for OUD. Results: Fifteen opioid craving assessment instruments were identified across the 87 studies included for review. The most common were the Visual Analog Scale (VAS, 41 studies), Desires for Drug Questionnaire (DDQ, 12 studies), Heroin Craving Questionnaire (HCQ, 10 studies), and Obsessive-Compulsive Drug Use Scale (OCDUS, 10 studies). Craving assessments varied considerably in their format, content, time frame, and underlying subscales, and only 6 of 15 had been psychometrically evaluated. Discussion: This review identified a variety of opioid craving assessments, but few had been evaluated for their psychometric properties making it difficult to ascertain whether craving is being assessed optimally in studies of OUD. Thus, the development of a reliable and valid opioid craving assessment would be worthwhile and could be guided by recently published Food and Drug Administration Clinical Outcome Assessment (COA) guidelines. Importantly, a COA focused on opioid craving could be a valuable addition to research studies designed to evaluate novel treatments for OUD.